Problem Solving Cases in MS Access & Excel, 16th Edition - Ellen Monk; Joseph Brady; Emilio Mendelsohn (Cengage Learning, 2019)
Learn how to analyze and successfully solve today's real business problems using the latest Microsoft Office Access database management system and the most recent version of Excel spreadsheet tools. Packed with hands-on learning opportunities, Monk/Brady/Mendelsohn's PROBLEM-SOLVING CASES IN MICROSOFT ACCESS AND EXCEL, 16E features five individual tutorials designed to build your practical knowledge as you walk step-by-step through the capabilities of each software application. Twelve all-new case studies challenge you to use the software applications to resolve scenarios and problems you are likely to encounter on the job. In addition, a unique emphasis on skill-building integration demonstrates how to use Access and Excel together to resolve challenges within each case. Trust today's most up-to-date, practical guide for mastering critical Access and Excel skills in a business context. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.